2013
DOI: 10.1097/id.0b013e3182818792
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins 1β and 10 Expressions in the Periimplant Crevicular Fluid From Patients With Untreated Periimplant Disease

Abstract: Lower IL-1β and higher IL-10 levels characterized healthy periimplant conditions, which demonstrate the anti-inflammatory predominance in sites without disease signs. IL-10 levels decrease significantly according to increase of disease status. Therefore, its levels can differentiate healthy, mucositis, and periimplantitis. Thin PP and HP are associated with periimplant disease. These findings suggest the use of ILs as a biochemical marker for early diagnosis of periimplant disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(97 citation statements)
references
References 31 publications
3
93
0
1
Order By: Relevance
“…Our findings confirmed those of many previous studies regarding the proinflammatory role of IL-1β11,15. In the current study, we assessed a healthy tooth, a healthy implant, and an implant with peri-implantitis all in the same patient as one important inclusion criterion.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings confirmed those of many previous studies regarding the proinflammatory role of IL-1β11,15. In the current study, we assessed a healthy tooth, a healthy implant, and an implant with peri-implantitis all in the same patient as one important inclusion criterion.…”
Section: Discussionsupporting
confidence: 90%
“…It was confirmed that higher concentrations of TNF-α, IL-17 and IL-1β are present in PICF collected from peri-implantitis-affected sites, compared to healthy controls (Ataoglu et al 2002;Curtis et al 1997;Darabi et al 2013;Vieira et al 2013;Severino et al 2011), whereas the opposite was the case for anti-inflammatory cytokine IL-10 (Casado et al 2013). More recently multiplex cytokine arrays have been applied in the analysis of PICF, allowing for a broader simultaneous screening of multiple inflammatory cytokines and chemokines.…”
mentioning
confidence: 61%
“…Concentrations of the classical anti-inflammatory cytokines IL-4 and IL-10 were analyzed in few studies. In implants with peri-implantitis, similar [57,58] or lower [55] levels of IL-4 and/or IL-10 were reported, despite that higher levels of IL-10 were also described [52]. …”
Section: Bone Cells Activity During Peri-implantitismentioning
confidence: 97%